2018
DOI: 10.1136/heartasia-2018-011038
|View full text |Cite
|
Sign up to set email alerts
|

Clinical implication of LAVI over A′ ratio in patients with acute coronary syndrome

Abstract: LAVI/A' was related to plasma BNP levels in patients with ACS, particularly in those with NSTE-ACS. This index was useful for predicting cardiac events in patients with ACS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…LA size is essentially governed by the factors that affect diastolic LV filling. Previous studies with conventional echocardiographic imaging have suggested that LA size, LV volumes indices, and LVEF were good predictors for monitoring cardiovascular risk and guiding therapy in patients with ACS [6,[16][17][18]. LV function evaluated with an echocardiogram before hospital discharge represents one of the strongest predictors of survival in ACS patients [19].…”
Section: Discussionmentioning
confidence: 99%
“…LA size is essentially governed by the factors that affect diastolic LV filling. Previous studies with conventional echocardiographic imaging have suggested that LA size, LV volumes indices, and LVEF were good predictors for monitoring cardiovascular risk and guiding therapy in patients with ACS [6,[16][17][18]. LV function evaluated with an echocardiogram before hospital discharge represents one of the strongest predictors of survival in ACS patients [19].…”
Section: Discussionmentioning
confidence: 99%
“…The herein proposed hierarchical approach to undetermined DF was similarly effective both for ASE/EACVI and for OH. Besides the well-known Valsalva maneuver and quantitative PVF assessment, we introduced LAVi/a’, which resulted in an increased rate of upgrading patients with undetermined DD [ 13 , 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…A relative decrease of 50% or an absolute decrease of 0.5 in the E/A ratio, based on each classification, were used as a highly specific feature for raised LV filling pressures. In addition, we decided to explore the potential role TDI a’, alone [ 20 , 21 , 22 ] or in combination with LAVi (LAVi/a’) [ 13 , 14 , 15 ] in re-classifying patients in the undetermined group.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[5] Therefore, indicators of LAE might be associated with diastolic dysfunction in patients with CAD to some extent, regardless of a reduced LVEF. [6] Left atrial volume index (LAVI) is a relatively easily available indicator of LAE. LAVI is also a powerful predictor of mortality in patients with acute coronary syndrome (ACS).…”
Section: Introductionmentioning
confidence: 99%